The Hero Archetype Analysis of Main Character in A Study in Scarlet - santi afrida rahmawati; Yulis Setyowati; Surya Priyambudi (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2024)
This research aims to analyze hero archetype of main character in A Study in Scarlet. This study explains the hero archetype of main character in A Study in Scarlet. The researcher uses a qualitative approach as a research method. The data source is A Study in Scarlet. Data collection by: (1) read comprehensively the novel (2) Collect and retrieve data from the novel relating to the research problem (3) Fragmenting dialogue in the novel according to the research problem (4) selecting the dialog that are the hero archetype. Meanwhile, the data analysis procedures are: (1) Selecting dialogs in the novel A study in Scarlet, (2) classifying the hero archetype based on objects of Carol Pearson's theory, such as the innocent, the warrior, the caregiver. (4) drawing a conclusion. This study shows that the appearance of the hero archetype in the main character there found A Study in Scarlet. The research delves into the profound exploration of the hero archetype as exemplified by the main character in Arthur Conan Doyle's